RTRW Policy Implementation Impact on Residential Environmental Quality in Padang Selatan District - Vira Cahayani Karmila; Sinta Westika Putri (Darul Yasin Al Sys, 2026)
The mismatch between spatial planning policies and the actual conditions of residential areas remains a fundamental challenge in many developing cities, including Padang Selatan District, Padang City. However, studies that specifically integrate the impacts of Regional Spatial Plan (RTRW) implementation with the actual environmental quality of residential areas in this region remain limited. This study aims to examine the impact of RTRW policy implementation under Padang City Regional Regulation No. 3 of 2019 on residential environmental quality and to analyze the supporting and inhibiting factors influencing its implementation. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document reviews in three study sites: Seberang Palinggam, Seberang Padang, and Air Manis. The analysis was guided by Agustino’s (2017) policy impact framework, which includes the dimensions of primary subjects, externalities, time, and costs. The findings indicate that the impact of RTRW implementation varies substantially across the three areas. Air Manis experienced the most significant changes, including building reorganization, drainage improvements, and enhanced accessibility, largely supported by organic incentives from its tourism zone. Seberang Padang showed partial improvements through the Kotaku program and central government funding amounting to Rp14.9 billion. In contrast, Seberang Palinggam experienced almost no formal policy impact because approximately 80–90% of its land is classified as perponding land, making standard building permit mechanisms difficult to apply. Supporting factors include subdistrict monitoring teams, coordination through the PKP Working Group Forum, commitment from government officials, and tourism-based incentives. The main constraints include unclear land ownership status, reactive monitoring practices, low spatial planning literacy, urbanization pressures, limited community economic capacity, and weak policy outreach. This study concludes that effective RTRW implementation in residential areas depends on resolving agrarian issues as a primary prerequisite, balancing investment between physical development and monitoring capacity, and integrating economic incentives into policy implementation strategies. The findings contribute to spatial planning and urban governance studies by demonstrating that regulatory implementation is shaped not only by formal policy design but also by land tenure clarity, local institutional capacity, and socio-economic conditions.